(untitled) (Biological Sciences - PJSIR, 1996)
2-Methylchromones Ja-d were converted to 4-methyl-6-(substituted phenyl) -2-[1 H]-thiopyrimidines IIa-d, via the condensation with thiourea. These thiopyrimidines were converted to other pyrimidine derivatives e.g. bis pyrimidinyl disulphides, oxopyrimidines, ethoxycarbonylmethylmercaptopyrimidines, ethoxycarbonylmethyl- mercaptopyrimidine acid hydrazides, triazolylpyrimidines, pyrimidin-2-ylmercaptoacetyl-thiosemicarbazides and dimethyl oxalacetate 2-carboxymethyl-mercaptopyrimidine acid hydrazides.